Experimental challenges to stiffness as a transport paradigm. (4th January 2018) - Luce, T.C.; Burrell, K.H.; Holland, C.; Marinoni, A.; Petty, C.C.; Smith, S.P.; Austin, M.E.; Grierson, B.A.; Zeng, L.
Abstract: Two power scans were carried out in H-mode plasmas in DIII-D; one employed standard co-current neutral beam injection (NBI), while the other used a mixture of co-current and counter-current NBI to scan power while holding the torque to a low fixed value. Analysis of the ion and electron heat transport, ion toroidal angular momentum transport, and thermal deuterium transport from these scans is presented. Invariance of the gradients or gradient scalelengths, as might be expected from stiff transport, was not generally observed. When invariance was seen, it was not accompanied by a strong increase in transport, except in the case of the absolute deuterium ion transport. Conduction in the ion channel is the dominant energy loss mechanism. The variation of the ion heat transport with applied power is similar for the co-injection and fixed torque scans, indicating that E   ×   B shearing is not determining the plasma response to additional power. There is however, a quantitative difference in the transport between the two scans, indicating E   ×   B shearing does play a role in the transport. Comparison of these results with a previous experiment that directly probed stiffness at a single radius leads to the following conclusion: while local stiffness as formally defined may hold, invariance of the gradients or normalized scalelengths does not follow from stiff transport in more practical scaling experiments, such as the power scans discussed here. Possible reasons for the lack of correspondence between the local picture and the global expectations are discussed.